2016
DOI: 10.1002/anie.201610455
|View full text |Cite
|
Sign up to set email alerts
|

N,P‐Heterocyclic Germylene/B(C6F5)3 Adducts: A Lewis Pair with Multi‐reactive Sites

Abstract: An N,P-heterocyclic germylene/B(C F ) Lewis adduct 2 presenting multi-reactive sites (P/B Lewis pair, germylene, Ge=P π-bond) is reported. In contrast to classical frustrated Lewis pairs or divalent Group 14 element species, 2 is able to activate two small molecules simultaneously. Of particular interest, 2 reacts with silanes leading to the formation of original cationic germylenes 3, and can be used as a metal-free catalyst for selective CO -hydrosilylation to H C(OSiEt ) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 78 publications
2
28
0
Order By: Relevance
“…Outer‐sphere hydride transfer that does not involve LA activation has also been discussed, mainly for CO 2 hydrogenation processes . In some main‐group catalyst systems, direct H − transfer from E−H to free or LA‐activated CO 2 has also been proposed …”
Section: Activation Modes For the Si−h Bond And Co2mentioning
confidence: 79%
See 1 more Smart Citation
“…Outer‐sphere hydride transfer that does not involve LA activation has also been discussed, mainly for CO 2 hydrogenation processes . In some main‐group catalyst systems, direct H − transfer from E−H to free or LA‐activated CO 2 has also been proposed …”
Section: Activation Modes For the Si−h Bond And Co2mentioning
confidence: 79%
“…In 2018, Kato et al. reported that an N,P‐heterocyclic germylene/B(C 6 F 5 ) 3 Lewis pair ( 44 ) exhibited multisite reactivity and the ability to readily cleave a Si−H bond of hydrosilanes into a highly reactive cationic silylated germylenes and an anionic hydridodoborate pair . Such an ion pair can subsequently deliver the formal hydride and silylium ions to CO 2 two times to give the selective formation of the bis(silyl)acetal reduction product (Scheme ).…”
Section: Main‐group Catalysismentioning
confidence: 98%
“…The use of 2‐H to catalyse the hydrosilylation of CO 2 represents a relatively rare example of the use of a main group hydride as a catalyst for this process [57, 58, 68] . That this system can be used to selectively generate (Et 3 SiO) 2 CH 2 , a potential source of formaldehyde, led us to investigate how this transformation proceeds.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a variety of homogenous catalytic systems based on metals (Pd/Pt, [14–17] Rh, [18] Re, [19, 20] Ru, [21–26] Ir, [8, 27–30] Co, [13, 31] Mn, [12] Zr, [32, 33] Cu, [34–38] Ni, [39–42] Sc, [43–46] Zn, [47–57] Mg [57, 58] and Sr [59] ), Lewis acids, [60–66] frustrated Lewis pairs (FLPs), [67, 68] organo‐catalysts, [69–75] alkali metal carbonates, [76, 77] and metal borohydrides [78] have been investigated for this process. Many of these catalytic systems feature reactive metal hydride or alkyl groups, which effect the initial activation of CO 2 via insertion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation